Modulation of Adaptive Immunity and Viral Infections by Ion Channels - Bohmwald, Karen; Gálvez, Nicolás M. S.; Andrade, Catalina A.; Mora, Valentina P.; Muñoz, José T.; González, Pablo A.; Riedel, Claudia A.; Kalergis, Alexis M. (Frontiers in Physiology, 2021)
Most cellular functions require of ion homeostasis and ion movement. Among others, ion channels play a crucial role in controlling the homeostasis of anions and cations concentration between the extracellular and intracellular compartments. Calcium (Ca2+) is one of the most relevant ions involved in regulating critical functions of immune cells, allowing the appropriate development of immune cell responses against pathogens and tumor cells. Due to the importance of Ca2+ in inducing the immune response, some viruses have evolved mechanisms to modulate intracellular Ca2+ concentrations and the mobilization of this cation through Ca2+ channels to increase their infectivity and to evade the immune system using different mechanisms. For instance, some viral infections require the influx of Ca2+ through ionic channels as a first step to enter the cell, as well as their replication and budding. Moreover, through the expression of viral proteins on the surface of infected cells, Ca2+ channels function can be altered, enhancing the pathogen evasion of the adaptive immune response. In this article, we review those ion channels and ion transporters that are essential for the function of immune cells. Specifically, cation channels and Ca2+ channels in the context of viral infections and their contribution to the modulation of adaptive immune responses.